2019
DOI: 10.1002/chem.201901457
|View full text |Cite
|
Sign up to set email alerts
|

Cyclization of Terphenyl‐Bisfluorenols: A Mechanistic Study of the Regioselectvity

Abstract: The mechanism of the bicyclization reaction of a series of terphenyl‐bisfluorenols into dispiro[fluorene‐9,6′‐indeno[1,2‐b]fluorene‐12′,9′′‐fluorene] and dispiro[fluorene‐9,6′‐indeno[2,1‐a]fluorene‐12′,9′′‐fluorene] is reported. Through a combined experimental and theoretical study, the different parameters that drive the regioselectivity of this cyclization reaction have been studied and are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 59 publications
0
13
0
Order By: Relevance
“…Interestingly, the 1 H NMR signal of the hydrogen atom in the position 14 in 2 appears as a doublet of doublets with the coupling constants of 3 and 8 Hz. Additional 1 H spectra measured with simultaneous 19 F decoupling revealed that the additional 3 Hz coupling comes from the throughspace interaction with fluorine in the position 1. It corresponds with the close contact of these atoms in space leading to an overlap of their electron clouds.…”
Section: Synthesis Of Fluorinated Dihydroindenofluorenesmentioning
confidence: 97%
See 3 more Smart Citations
“…Interestingly, the 1 H NMR signal of the hydrogen atom in the position 14 in 2 appears as a doublet of doublets with the coupling constants of 3 and 8 Hz. Additional 1 H spectra measured with simultaneous 19 F decoupling revealed that the additional 3 Hz coupling comes from the throughspace interaction with fluorine in the position 1. It corresponds with the close contact of these atoms in space leading to an overlap of their electron clouds.…”
Section: Synthesis Of Fluorinated Dihydroindenofluorenesmentioning
confidence: 97%
“…The cyclotrimerization of 8 c gave rise to diol 10 c, which was isolated in 50 % (Scheme 3, conditions A). It should be noted that formation of other intractable side-products was noticed by 19 F NMR analysis of the crude reaction mixture. Lowering of the reaction temperature to 150°C provided 10 c in 76 % yield (conditions B), along with reduced formation of other side-products (again confirmed by 19 F NMR analysis of the crude mixture).…”
Section: Synthesis Of Fluorinated Dihydroindenofluorenesmentioning
confidence: 99%
See 2 more Smart Citations
“…In the field of organic semiconductors for electronics, the synthetic approach is of key importance . Indeed, for potential industrial applications, the synthesis of the host material for a PhOLED should be short, high yielding, and should use inexpensive starting materials.…”
Section: Synthesismentioning
confidence: 99%